Tenth IEEE International Conference on Computer Vision (ICCV'05) Volume 1 2005
DOI: 10.1109/iccv.2005.79
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic refraction stereo

Abstract: In this paper we consider the problem of reconstructing the 3D position and surface normal of points on an unknown, arbitrarily-shaped refractive surface. We show that two viewpoints are sufficient to solve this problem in the general case, even if the refractive index is unknown. The key requirements are (1) knowledge of a function that maps each point on the two image planes to a known 3D point that refracts to it, and (2) light is refracted only once. We apply this result to the problem of reconstructing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 22 publications
(5 reference statements)
1
58
0
Order By: Relevance
“…Kutulakos et al [5] investigate the geometry of light-path triangulation, which aims to find conditions and algorithms where reconstruction of individual tracks of light is possible. The work of Morris and Kutulakos [8] looks at refractive stereo. The main idea here is to estimate the normal of the refractive surface, given 2D-3D correspondences, irrespective of the refractive index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kutulakos et al [5] investigate the geometry of light-path triangulation, which aims to find conditions and algorithms where reconstruction of individual tracks of light is possible. The work of Morris and Kutulakos [8] looks at refractive stereo. The main idea here is to estimate the normal of the refractive surface, given 2D-3D correspondences, irrespective of the refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the study of this change had been restricted to multimedia photogrammetry [7] and oceanic engineering [9], where the major perspectives were to either neglect the refraction [3,9], view refraction as an error or aberration to perspective imaging [12,10], or to look at its correction as an iterative optimization problem [7]. In computer vision, some of the first attempts have come in the recent past [5,8,1,15,6]. Kutulakos et al [5] investigate the geometry of light-path triangulation, which aims to find conditions and algorithms where reconstruction of individual tracks of light is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that it is possible to recover the shape of the surface of an air-water interface by filming a textured background underneath it [9,16,30]. Alterman et al [4] proposed to recover refraction location and strength from multiple cameras using tomography.…”
Section: Related Workmentioning
confidence: 99%
“…To recover the water geometry in real time, a theoretical work by Dolin [16] hypothesizes that the WAI slope can be inferred by its specular reflection 1 of a cloudless sky. Multicamera methods have also been applied to WAI recovery [15], [33], [37], [38], [49]. A critical review of passive approaches to recover the WAI is in [22].…”
Section: Related Work: Vision Via a Waimentioning
confidence: 99%